H-Ras Exerts Opposing Effects on Type I Interferon Responses Depending on Its Activation Status - Chen, Guann-An; Lin, Yun-Ru; Chung, Hai-Ting; Hwang, Lih-Hwa (Frontiers in Immunology, 2017)
Using shRNA high-throughput screening, we identified H-Ras as a regulator of antiviral activity, whose depletion could enhance Sindbis virus replication. Further analyses indicated that depletion of H-Ras results in a robust increase in vesicular stomatitis virus infection and a decrease in Sendai virus (SeV)-induced RIG-I-like receptor (RLR) signaling. Interestingly, however, ectopic expression of wild-type H-Ras results in a biphasic mode of RLR signaling regulation: while low-level expression of H-Ras enhances SeV-induced RLR signaling, high-level expression of H-Ras significantly inhibits this signaling. The inhibitory effects correlate with the activation status of H-Ras. As a result, oncogenic H-Ras, H-RasV12, strongly inhibits SeV-induced IFN-β promoter activity and type I interferon (IFN-I) signaling. Conversely, the positive effects exerted by H-Ras on RLR signaling is independent of its signaling activity, as a constitutively inactive form of H-Ras, H-RasN17, also positively regulates RLR signaling. Mechanistically, we demonstrate that depletion of H-Ras reduces the formation of MAVS-TRAF3 signaling complexes. These results reveal that the H-Ras protein plays a role in promoting MAVS signalosome assembly in the mitochondria, whereas oncogenic H-Ras exerts a negative effect on type I IFN responses.